Unknotting the heart : unemployment and therapeutic governance in China - Yang, Jie, 1970- (ILR Press, an imprint of Cornell University Press, 2015)
Since the mid-1990s, as China has downsized and privatized its state-owned enterprises, severe unemployment has created a new class of urban poor and widespread social and psychological disorders. In Unknotting the Heart, Jie Yang examines this understudied group of workers and their experiences of being laid off, "counseled," and then reoriented to the market economy. Using fieldwork from reemployment programs, community psychosocial work, and psychotherapy training sessions in Beijing between 2002 and 2013, Yang highlights the role of psychology in state-led interventions to alleviate the effects of mass unemployment. She pays particular attention to those programs that train laid-off workers in basic psychology and then reemploy them as informal "counselors" in their capacity as housemaids and taxi drivers. These laid-off workers are filling a niche market created by both economic restructuring and the shortage of professional counselors in China, helping the government to defuse intensified class tension and present itself as a nurturing and kindly power. In reality, Yang argues, this process creates both new political complicity and new conflicts, often along gender lines. Women are forced to use the moral virtues and work ethics valued under the former socialist system, as well as their experiences of overcoming depression and suffering, as resources for their new psychological care work. Yang focuses on how the emotions, potentials, and "hearts" of these women have become sites of regulation, market expansion, and political imagination